Aplikasi Absensi Siswa Menggunakan Teknologi Radio Frequency Identification (Rfid) Berbasis Node Mcu - Juwanda Juwanda; Arip Solehudin; Didi Juardi (Peneliti.net, 2023)
The student attendance application is a list of student attendance which is one of the important aspects that support the running of the learning system. In schools that still use the manual attendance system, that is, attending students one by one. This manual attendance system has a weakness that is not practical. Things that are not practical in this system can be in the form of spending a lot of time to attend students one by one or the process of recording data to the center which is complicated because it is done manually, attendance data at the center cannot be directly updated because they have to wait to be recapitulated by the officer concerned. Currently, technology has developed very rapidly, one of which is RFID (Radio Freequency Identification) technology, a technology that uses radio waves to identify an object automatically. RFID (Radio Freequency Identification) began to be developed as a new technology that will facilitate human work to identify various things, for example in the development of student attendance applications using RFID it makes it easier for teachers to find information, this can save time and is very efficient for use by parties. schools can also get a definite picture of student attendance data.